Parceria público-privada como política pública educacional e a diversidade étnico-racial - Alves, Carmem Dolores (2019)
This Study is part of the Public Educational Policies and Ethnic-Racial Diversity. Our aim was to analyse the Public-Private Relationship(PPR) in the respective Aprova Recife Project and Literacy Program- PROLER ,of Education Secretary of Recife and its impact on the Ethnic-Racial Diversity Axis ,as an integral part of Education Policy .The object investigated emerges from a historical context of advances and setbacks that point to difficulties in institutionalizing policies to promote racial equality and antiracist education, placing it at a global political moment of conflicts about the paradigm aimed the valuing of diversity and re-education of ethnic-racial relations, as well as between groups with racial distinctions. We underline the relevance of this Study under the following aspects: to provide subsidies for future academic studies in the area of educational policy under the managerial model in driving of public education; collaborate to research on racism and ethnic-racial relations ,highlighting the process of exclusion of the black population from education. For the purpose of this Study, we used the theoretical support of neoliberalism, managerialism and an analysis of the role of public power and the private initiative from Gramsci thinking (2001),with emphasis on the concepts of hegemony, organic intelectual and contradiction. The research was of the descriptive exploratory type under a qualitative approach .For data analysis we adopted the theoretical-methodological perspective of Bardin(2009).The results pointed to a phenomenon that favored the emptying of the Ethnic-Racial Diversity Axis according to the hegemonic managerial model, anchored in the neoliberal project, which was configurated through multiple and complex issues, emphazing the gradual modification of the schools of the Municipal Education Network of Recife in administrative units, in which the public-private delimitation is not perceived in daily school; the commitment of the teacher autonomy; acceptance of the public-private in the curriculum, in the formation and in the daily school; educational management of the municipality ,which pedagogical purposal brings in the quantitative overlaid the qualitative ,disregarding diversity as priority; and the incidence of the private Projects and Programs that should be consonant with the Education Policy and the Diversity Axis. The hegemony of these private Project and Program inhibited the materialization and consolidation of the Ethnic-Racial Diversity Axis and subsequent potential construction of an anti-racist education.